Impatiens pseudolaevigata Gogoi, B. B. T. Tham & Lidén (Balsaminaceae): a new record to the flora of Bhutan - Jamtsho, Sherab; Gyeltshen, Phub; Wangchuk, Sangay; Subba, Dhan Bahadur (Biodiversity: Research and Conservation, 2023)
Impatiens pseudolaevigata Gogoi, B. B. T. Tham & Lidén was collected in August 2019 from the broadleaved forest of Zhemgang district, and is reported as new to the flora of Bhutan. Detailed descriptions, remarks on ecology, field notes, and images of the species are provided.